Tinjauan Yuridis Prinsip Pemilik Manfaat (Benefit Ownership) Dalam Hukum Pidana Korporasi - Akmal; Abdaud, Faisal; Huzaiman (Lex Stricta : Jurnal Ilmu Hukum, 2025)
In the era of globalisation, corporations are often involved in criminal acts such as corruption and money laundering, making it important to understand the role of beneficial ownership principles in corporate criminal law in Indonesia. This study aims to analyse the application of beneficial ownership principles, the challenges faced, and their implications for accountability and transparency in corporate governance practices. This study uses a normative research method with a legislative and conceptual approach. The results show that although Presidential Regulation No. 13 of 2018 requires the disclosure of beneficial owners, there is still ambiguity in the definition and a lack of strict sanctions that hinder the effective application of this principle. Identifying beneficial owners can increase transparency and accountability, but challenges in law enforcement remain, including complex ownership structures that make it difficult to identify responsible individuals. This study recommends legal reforms to strengthen corporate responsibility and improve law enforcement understanding of the application of the beneficial ownership principle.